O uso da teoria de conjuntos aproximados na modelagem de bases de dados relacionais e na extração de conhecimento - Vieira, João Marcos (Universidade Federal de São Carlos, 2005)
This work investigates two relational database models that extend the standard relational database model. Both models extend the standard relational model by allowing ways to represent uncertainty. The rough relational database model borrows the basic concepts form the rough set theory and deals with uncertainty by approaching relations using their lower and upper approximations. The fuzzy rough relational database model generalizes the rough relational model by introducing a degree of membership associated to elements, in a rough relation. The operators that are an intrinsic part of each of the models are formally defined and their pseudocodes are presented and discussed in details. A prototype system ROUGH-ID3, which implements a hybrid knowledge extraction approach by integrating a set of rough database operators with the symbolic system ID3 is proposed.
Keywords: Inteligência artificial; Base de dados relacional aproximada; Conjuntos aproximados; Sistema colaborativo aproximado-simbólico; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO